Pengaruh Kompetensi Sumber Daya Manusia dan Peran Audit Internal terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Maria Jali Yanti Nahak; Fransisco Nyongki Mura; Susana Purnama Sari Baso (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The quality of local government financial statements is a key indicator of accountability and transparency in public financial management. In practice, however, problems such as recording errors, non-compliance with accounting standards, and weak internal oversight are still frequently encountered. This study aims to examine the effect of human resource competence and the role of internal audit on the quality of local government financial statements. A quantitative approach was employed using a survey method, with primary data collected through questionnaires distributed to employees involved in financial management and internal supervision within local governments. The data were analyzed using multiple linear regression after conducting data quality tests and classical assumption tests. The results indicate that human resource competence has a positive and significant effect on the quality of financial statements, suggesting that employees’ knowledge, skills, and experience play an essential role in producing reliable financial reports. Furthermore, the role of internal audit is also found to have a positive and significant effect by strengthening supervision, evaluation, and internal control processes. These findings emphasize that improving the quality of local government financial reporting requires both enhanced human resource capacity and effective internal audit functions.